2018
DOI: 10.51386/25815946/ijsms-v1i4p106
|View full text |Cite
|
Sign up to set email alerts
|

Fraud Detection and Internal Control Measures in Deposit Money Banks Listed on the NSE

Abstract: This study examine the internal control measures for fraud prevention and detection in Deposit Money Banks (DMBs) listed on the Nigerian Stock Exchange (NSE). Data collected were from both primary and secondary sources using annual financial reports and questionnaire for the respondents of all listed DMBs in Nigeria. Analysis was mainly done by regression of the internal control measures and fraud in DMBs. Internal control measures proxies are control environment, risk assessment and control activities. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
3
0
3
Order By: Relevance
“…The study found that a significant positive relationship exists between ICS and fraud detection and prevention in sub-county treasuries in Kakamega County. Haladu (2018) conducted a study on fraud detection and internal control measures within Nigerian Stock Exchange (NSE)-listed deposit money banks (DMBs). Employing both survey and ex-post factor research designs, the study encompassed all 15 banks listed by the NSE as of the 2017 financial year.…”
Section: Effect Of Ics On Fraud Preventionmentioning
confidence: 99%
“…The study found that a significant positive relationship exists between ICS and fraud detection and prevention in sub-county treasuries in Kakamega County. Haladu (2018) conducted a study on fraud detection and internal control measures within Nigerian Stock Exchange (NSE)-listed deposit money banks (DMBs). Employing both survey and ex-post factor research designs, the study encompassed all 15 banks listed by the NSE as of the 2017 financial year.…”
Section: Effect Of Ics On Fraud Preventionmentioning
confidence: 99%
“…Hal tersebut berarti semakin efektif sistem pengendalian internal maka tingkat kecenderungan kecurangan semakin menurun. Haladu [10] dalam penelitiannya menemukan bahwa pengendalian internal berpengaruh negatif terhadap fraud detection. Artinya semakin kuat pengendalian internal internal maka semakin sedikit ditemukan adanya fraud.…”
Section: 6unclassified
“…Penelitian ini sejalan dengan hasil penelitian Suastawan dkk, [21], Udayani dan Sari [23], yang menjelaskan bahwa sistem pengendalian internal berpengaruh positif terhadap fraud prevention. Hasil penelitian lain yang dilakukan oleh Haladu [10] menjelaskan bahwa sistem pengendalian internal berpengaruh negatif terhadap fraud detection, yang artinya semakin kuat pengendalian internal maka semakin sedikit ditemukan adanya fraud. Sistem pengendalian internal yang baik mampu menghilangkan praktik-praktik kecurangan.…”
Section: Pengaruh Sistem Pengendalian Internal Terhadap Fraud Preventionunclassified
See 1 more Smart Citation
“…Over the years, auditing has been deployed in business to detect errors and fraud early and offer actual views about financial information (Alao, 2016;Emmanuel et al, 2013;Haladu, 2018;Ogoun & Atagboro, 2020;Oyerogba, 2021). Nevertheless, auditing small and medium-scale businesses in Nigeria has been fraught with the inadequacy of internal controls.…”
mentioning
confidence: 99%